Stigma towards PLWHA: The Role of Internalized Homosexual Stigma in Latino Gay/Bisexual Male and Transgender Communities - Ramirez-Valles, Jesus (2013)
Stigma negatively affects the health of people living with HIV/AIDS (PLWHA). Negative attitudes and discriminatory actions towards PLWHA are thought to be based, among other factors, on stigma towards sexual minorities and beliefs about personal responsibility. Yet, there is little evidence to support these linkages and explain how they take place, especially among Latinos. This study analyzes attitudes towards PLWHA among 643 Latino gay/bisexual men and transgender (GBT) people. It examines whether discriminatory actions are predicted by beliefs about personal responsibility and internalized homosexual stigma. Results indicate that Discriminatory Actions towards PLWHA is associated with HIV/AIDS Personal Responsibility Beliefs and Internalized Homosexual Stigma. Further, HIV/AIDS Personal Responsibility Beliefs partially mediates the relationship between Internalized Homosexual Stigma and Discriminatory Actions towards PLWHA. Latino GBT persons who have internalized negative views about homosexuality may project those onto PLWHA. They may think PLWHA are responsible for their serostatus and, hence, deserving of rejection.